Revolutionizing Credit Dispute Resolution: Balancing Creditors and Debtors Interests for Greater Efficiency - Jeremia, Mario Ihutan; Sukarmi, Sukarmi; Sihabudin, Sihabudin; Santoso, Budi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
Non-performing loans (NPLs) strain creditor-debtor relationships, jeopardizing economic stability. Traditional dispute resolution methods are costly, time-consuming, and often fail to meet the needs of both parties. This paper introduces a novel, efficiency-based approach to NPL dispute resolution, grounded in economic analysis of law. By optimizing resource allocation, it minimizes transaction costs and resolution time, benefiting both creditors and debtors. Using a qualitative and normative methodology, the study explores the application of efficiency principles in Indonesia. The findings highlight that an efficient dispute resolution paradigm can enhance outcomes, foster trust in the banking system, and provide economic benefits. The paper advocates for legal reforms to promote mediation and arbitration, ensuring faster, cost-effective, and sustainable solutions to NPL disputes.